Pengaruh Literasi Keuangan, Digital Marketing, Dan Word Of Mouth Terhadap Minat Generasi Z Menabung Pada Bank Syariah (Studi Kasus Masyarakat Binjai Kota) - Yuli Sahara Nst; Siti Mujiatun (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2026)
This research was conducted with the aim of analyzing the effect of financial literacy, digital marketing, and word of mouth on the z generation's interest in saving at Islamic banks. The research method used in this study is quantitative research and data collection techniques in this study using a questionnaire. The data analysis used in this research is data quality test, classic assumption test, multiple linear regression test, hypothesis test and determination test. Based on the results of the study, it shows that the Financial Literacy variable (X1) has a positive and significant effect on the Z generation interest variable in saving at Islamic banks (Y) by obtaining tcount (3.340) >ttable (1.984) with a significant value of 0.001 <0.05, Digital Marketing variable (X2) has a positive and significant effect on the z generation interest variable in saving at Islamic banks (Y) by obtaining tcount (4.708) > ttable (1.984) with a significant value of 0.000 <0.05, word of mouth variable (X3) has a positive and significant effect on the z generation's interest in saving at Islamic banks (Y) by obtaining tcount (2.735) >ttable (1.983) with a significant value of 0.007 < 0.05, test simultaneously on the Financial Literacy variable (X1), Digital Marketing (X2), and Word Of Mouth (X3) state that there is a jointly significant effect on the z generation's interest in saving at Islamic banks (Y) by obtaining Fcount (86.492) >Â  Ftable (2.70) with a significant level of 0.000.